Leadership Behaviour and Human Resource Management Practice Mediation between Strategic Plan and Performance of Selected Ethiopian Sports Federation - Samson Tadesse; Tesfay Asgedom; Aschenaki Taddese (Universitas Majalengka, 2023)
The purpose of the study was to identify the relationship between strategic plan and performance through leadership behavior and human resource management practices (HRMP) of a selected Ethiopian sports federation. For this study's purpose, the researcher used quantitative research and a cross-sectional research design. A sample size of ninety-five (n = 95) respondents was used in this study. The quantitative data analysis was processed using IBM SPSS Amos 23.0 software. Structural equation modeling has been used to study this relationship. Confirmatory Factory Analysis (CFA) was used to test the hypothesis between strategic plan and performance through leadership behavior and human resource management practices of a selected Ethiopian sports federation. The result of the study shows leadership behavior and HRMP play an important mediating role between strategic plans and the performance of sport federations ( =.86, P = 0.00). The findings of the study confirm that leadership behavior and HRMP partially mediate the relationship between strategic plan and performance in both federations. The study recommended that it is advisable that selected Ethiopian sports federations work on capacity development programs for human resource development and take up-to-date leadership training frequently; this will enhance the performance of both federations.